An Overview of Tickborne Infections in Pregnancy and Outcomes in the Newborn: The Need for Prospective Studies - Lambert, John S. (Frontiers in Medicine, 2020)
Tick-borne infections are an ever increasing issue internationally, many factors contribute to this including a changing climate. Pregnant women represent the single largest vulnerable group in populations due to a relative immune deficiency status. Infections in pregnant women have the added gravity of potential infection in the developing fetus which may have catastrophic consequences including death in-utero or lifelong debilitation. Currently there is a paucity of data surrounding tick-borne infections in pregnancy and long term outcomes for mother and infant for conditions like Lyme disease and co-infections. At present there are no established international surveillance systems to identify and gain understanding of these infections in pregnancy. Furthermore the removal of Congenital Lyme Disease from ICD-11 codes hampers dialogue and characterization of borreliosis in pregnancy and stifles future developments of this understudied domain. This review makes the case for further study and re-opening a dialogue of tick borne infections in pregnacy